Computer-aided evaluation of television instruction in a tertiary-level introductory statistics course - Young, Derrick Aubrey (My University, 2014)
This study investigated the effectiveness of televised lectures in teaching an introductory statistics course to first year commerce undergraduates, Certain constraints imposed themselves on this introductory course which dictated many of the teaching conditions. Some of these conditions were that the lecture situation formed the major teaching component in the course and that these lectures were administered to large numbers of students (groups of between 70 and 120). The primary aim of the investigation was to determine whether or not the effectiveness of these lectures (when televised) could be assessed. A secondary aim was to determine whether or not (once the effectiveness of the lectures had been assessed) the areas in the lectures which had been identified as ineffective, could be analysed and changed, so as to become effective. In order to conduct this investigation the method employed demanded that three preliminary areas be fully expounded. The first was that the meaning of 'instructional effectiveness' be fully defined in terms of the previling conditions. In order to achieve this a criterion referenced approach to instruction was adapted to the television lectures. Secondly, the 'type' of television lecture had to be disclosed. The televised lectures were traditional in that they were similar to die 'live' lectures except for a few novel innovations. The study did not however set out to compare the effectiveness of the 'live and 'T.V,1 instruction - a point which is fully discussed in the second and sixth chapters, The third preliminary area was the means employed to collect the data which was needed for the evaluation of the lectures. A recently devoWpcd educational computer system was used for this purpose and a full description of this novel system is given in this study. The experimentation was based on two important premises. First, the evaluative means which were used to assess the lectures had to be valid. In other words they had to measure what they were supposed to iii. measure. The validation procedure, adopted is therefore fully discussed. Secondly the variables had to be Identified and controlled when improvements were attempted so as to ensure that the only variable which was allowed to change was the instruction. This procedure is always a difficult one and is fully discussed in chapter six and chapter eight. The results of this investigation indicated that it was both possible to assess and improve the effectiveness of a televised lecture within the prevailing conditions. However this investigation is seen only as a preliminary study into an area which requires scientifically based analyses and conclusions in order to achieve both effective and efficient instruction in this teaching area. Therefore there is much which this study did not do and several criticisms are made in the final chapter.
Thesis (M.Ed.)--University of the Witwatersrand, Faculty of Education, 1979.
Keywords: Television in education--South Africa